2010
DOI: 10.1242/dmm.001040
|View full text |Cite
|
Sign up to set email alerts
|

The role of insulin/IGF-like signaling in C. elegans longevity and aging

Abstract: Aging is characterized by general physiological decline over time. A hallmark of human senescence is the onset of various age-related afflictions including neurodegeneration, cardiovascular disease and cancer. Although environmental and stochastic factors undoubtedly contribute to the increased incidence of disease with age, recent studies suggest that intrinsic genetic determinants govern both life span and overall health. Current aging research aims at achieving the ‘longevity dividend’, in which life span e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
67
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(70 citation statements)
references
References 71 publications
2
67
0
1
Order By: Relevance
“…(Adams et al, 2000)]. Previous evidence, mainly from mutational studies, suggests that longevity can also be affected -with mutations in the genes relating to these two receptors seen to extend longevity [for example (Kaletsky and Murphy 2010;Junnila et al, 2013)]. …”
Section: The Wider Roles Of Ghr and Igf1r In Mammalsmentioning
confidence: 99%
“…(Adams et al, 2000)]. Previous evidence, mainly from mutational studies, suggests that longevity can also be affected -with mutations in the genes relating to these two receptors seen to extend longevity [for example (Kaletsky and Murphy 2010;Junnila et al, 2013)]. …”
Section: The Wider Roles Of Ghr and Igf1r In Mammalsmentioning
confidence: 99%
“…Studies show that increased longevity resulting from decreased Insulin/ IGF signaling is mediated to a great extent by FOXO and on the other hand, insulin/ IGF pathway accelerates aging by signaling to TOR. [113][114][115][116][117][118] The insulin-like receptor pathway has a large number of downstream transcriptional targets through which it may affect aging. These targets, which have been identified in various organisms, include antioxidant, chaperone, apolipoprotein, amino acid turnover and antibacterial genes, such as superoxide dismutase, metallothionine, catalase and glutathionine S-transferase, 117,[119][120][121][122][123][124] and collectively suggest that nutritional intake and growth signaling are related to ROS and DNA damage.…”
Section: Global Heterochromatin Lossmentioning
confidence: 99%
“…Mutations in daf-2 and age-1 extend life span more than double times in worms [62]. Subsequent research lead to the discovery of Insulin/insulin-like growth factor signalling pathway (IIS) and its role in regulating daf-2, age-1 and daf-16 in longevity.…”
Section: Paradox Of Insulin/igf-1 Signalling In Regulation Of Ageing mentioning
confidence: 99%
“…Not surprisingly, recent studies have suggested that genetic variants of human klotho gene and insulin signalling molecules are associated with ageing and extended life span. Further mutation in FOXO3A (human homolog of DAF-16) are found to increase longevity [62]. IGF-1 receptor mutation has been identified in centenarians from different ethnic groups and thus, correlating the increase in longevity and reduction of IGF-1 signalling [72].…”
Section: Paradox Of Insulin/igf-1 Signalling In Regulation Of Ageing mentioning
confidence: 99%